(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2022)
The mestizo-indigenous people, demographically hegemonic in Peru, have been integrated into the social, economic and political life of the country. Among many factors it is believed that the bricheros, classified within sex tourism, contributed to repositioning the indigenous in the identity discourse. Literature and ethnography reveal that tourism favored the bricheros, who took advantage of their exoticism to seduce women from developed countries with the aim of living at their expense or leaving the country. Likewise, by revaluing their cultural identity, they consolidated the ethnically Andean, and represent the most dynamic and progressive social sector in Peru.